Comparative Analysis of the Physicochemical Properties of Fresh, Solar-Dried, Oven-Dried and Commercial Royal Gala Apple Snacks - Lisete Fernandes; Pedro B. Tavares; João Siopa; Carla Gonçalves; Fernando M. Nunes (Applied Sciences, 2025)
This study compares the physicochemical properties of Royal Gala apple snacks fresh and processed using different methods: solar-dried (SD), oven-dried at 65 °C (OD65°) and 85 °C (OD85°) and two commercial brands (CC—commercial apple C and CF—commercial apple F). Evaluated parameters included color, microstructure, acidity, sugar content, phenolic compounds, antioxidant activity, and the presence of heat-induced compounds such as 5-hydroxymethylfurfural (5-HMF) and acrylamide. Commercial samples showed more pronounced color changes and a denser microstructure, with higher browning index (BI) values. The ratio of soluble solids to titratable acidity, an indicator of sensory acceptance, was more influenced by drying methods than temperature. Total phenolic content was highest in fresh apples (123.68 mg GAE/100 g d.m.) and decreased across all drying methods, particularly in solar-dried (SD) samples (78.57 mg GAE/100 g d.m.). Antioxidant activity followed a similar trend, although SD samples performed better than expected, likely due to the retention of certain bioactive compounds. Fresh apples had the highest sugar content (43.25 mg/100 g d.m.), followed by CC (33.81 mg/100 g d.m.), OD65° (33.37 mg/100 g d.m.), CF (31.56 mg/100 g d.m.), OD85° (25.92 mg/100 g d.m.) and SD (25.01 mg/100 g d.m.). Commercial samples were sweeter and darker, with detectable levels of 5-HMF and acrylamide. The findings highlight that drying method significantly affects snack quality. While solar- and oven-dried samples better preserve bioactive compounds, industrial processes enhance sweetness and visual appeal but increase the formation of potentially undesirable compounds. These results are valuable for both consumers and producers aiming to balance sensory quality with nutritional and food safety considerations in dried apple products.